2009
DOI: 10.1007/s12098-009-0260-5
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and stress among adolescent students belonging to affluent families: A school-based study

Abstract: A significant proportion of the students were found to be having high levels of DAS and several important factors were found to be associated with them. Proactive steps at the school-level and community-level and steps for improved parent-adolescent communication are needed for amelioration of the problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
80
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 7 publications
(11 reference statements)
16
80
5
1
Order By: Relevance
“…The results obtained from the current study show that majority of the board exam going students (74%) experience moderate level of anxiety which is in agreement with previous studies conducted among school students [23]. Pressure from school and parents, the lengthy format of Indian state government board exams (3 h), and heavy subject contents are some important factors that contribute to increased anxiety among students [1].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results obtained from the current study show that majority of the board exam going students (74%) experience moderate level of anxiety which is in agreement with previous studies conducted among school students [23]. Pressure from school and parents, the lengthy format of Indian state government board exams (3 h), and heavy subject contents are some important factors that contribute to increased anxiety among students [1].…”
Section: Discussionsupporting
confidence: 89%
“…Pressure from school and parents, the lengthy format of Indian state government board exams (3 h), and heavy subject contents are some important factors that contribute to increased anxiety among students [1]. It is already reported that students from board exam going classes, the 10th and 12th, present significantly higher level of depression, anxiety, and stress compared to the students from 9th and 11th grade [23]. We further found that the anxiety levels manifested by 12th standard students are higher than students from 10th.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of previous studies performed all over the world also indicate a large proportions of adolescents having these psychiatric disorders. [1213141516171819] Similar to the prevalences found in our study, the prevalences of depression, anxiety, and stress were 41.5%, 66.2%, and 52.5% in a study conducted in Saudi Arabia[14] among secondary school girls. Bayram and Bilgel[18] found that the prevalences were 51.4%, 66.05%, and 39.4% among University students, whereas the prevalences were 51.3%, 33.1%, and 53.0% in a study conducted among UG MBBS students.…”
Section: Discussionsupporting
confidence: 82%
“…They found that all three were significantly correlated and depression was more among females (p=0.03). 11 While in our study mean age was 16.7 yrs(0.66) and 197 (50.6%) were males. Even in our study all three were significantly correlated with each other.…”
Section: Discussionmentioning
confidence: 40%